Strategic Human Resource Management and Theoretical Background; A Critical Review Perspective - Sajeevanie, T.L. (Proceedings of the Third Asia-Pacific Conference on Global Business, Economics, Finance and Banking (APISSingapore Conference), 17-19 July 2015, 2015)
Attached

Wright et al. (1992) have mentioned that the field o f Strategic Human Resource Management (SHRM) is lack o f a strong theoretical foundation. Resource Base View (RBV) and there are some other theories which are relevant to the area o f SHRM. The literature on HRM and performance can be divided into three main kinds o f theories; Universalistic, Contingency and Configurationally (Gooderham et al., 2008). Wright et al. (1992, p.303) have mentioned that “one o f the original and more popular theoretical models used in the SHRM literature is the Behavioral Perspective”. As they explained, this theory focuses on the mediator effect on the relationship between strategy and firm performance. On the other hand the agency/transaction cost theory approach to examining the problems o f human exchange are based in the fields o f finance and economics. According to Universalist principles there is a universal prescription or ‘one best way’ or a general pattern. Another important issue is although the best practice approach has considerable support, this approach is also criticized by different perspective in the literature. Meanwhile the contingency school has criticized best practice. However it is clear that there is no universal prescription o f SHRM practice that should be employed in each different context. In contrast to the Universalistic or best practice approach, the best fit approach adopts a contingency approach. The linkage between strategy and HRM has received extensive attention from contingency school o f through. After considering all o f the relevant theories it can be concluded that the highly relevant theory for SHRM research is RBV while other theories do facilitating and supporting.
Keywords: Strategic Human Resource Management; theory; Resource Base View